A Comparative Study of Condom Usage Among Men in Urban Poor Communities in Accra. - Schandorf, J.N.S (University of Ghana, 2015)
HIV/AIDS and increasing population levels are topical issues in Sub-Saharan Africa. Male condoms may be the solution to these two problems. The vulnerability of urban poor communities in Accra to these problems cannot be overlooked. It is essential to find out the level of male condom usage in such urban poor communities. This study primarily sought to compare male condom use among three urban poor communities in Accra. The study also investigated the influence of community of residence on male condom use. Data was sourced from the 2011 EDULINK Urban Health and Poverty Project Wave 2 conducted by United Nations Regional Institute for Population Studies. The communities are Agbogbloshie, Jamestown and Usshertown. The communities have relatively different levels of poverty. Agbogbloshie has the highest poverty level, Jamestown has the lowest level of poverty while poverty in Usshertown stands between the two other communities. Univariate analysis showed that Agbogbloshie had 34% male condom use, while Jamestown had 35.8% male condom use and Usshertown had 40.4% male condom use. The results indicated that there is a low rate of male condom use in the urban poor communities. However, Chi-square tests showed that there was no significant difference in male condom usage in the three urban poor communities. Multivariate analysis indicate that 31% of variations of male condom use in the urban poor communities could be explained by community of residence and other factors. Odds ratios show that men in Jamestown are 18.3% less likely to use a condom than men in Usshertown. The likelihood of men in Agbogbloshie to use a condom is 21.4% more than men in Usshertown. However, after controlling for the other background characteristics in the model, living in these urban poor communities has no significant relationship with male condom use. The results from the study indicate that it is necessary to include comprehensive sex education in the Junior and Senior High School curricula to orient young men early in life on the importance of male condom use. There is the need for more research on the reasons why men do not use condoms in their multiple sexual relations. This would give policy makers clear targets to reach in order to increase the levels of male condom usage in urban poor communities in Accra and by extension Ghana as a whole.
Thesis (MA) - University of Ghana, 2015